Design and develop a device for evaluating composite/ceramic moulding part quality - Tan, Leon Ming Yeow. (2011)
Determining the joint strength of composite can be tedious and often times requires substantial training before one could conduct such tests. The main objective of this project is to determine a non-destructive test method that is easy to use, cost effective, portable and produces instantaneous results.